Heterologous Expression of Argininosuccinate Synthase From Oenococcus oeni Enhances the Acid Resistance of Lactobacillus plantarum - Zhao, Hongyu; Liu, Longxiang; Peng, Shuai; Yuan, Lin; Li, Hua; Wang, Hua (Frontiers in Microbiology, 2019)
Oenococcus oeni can survive well in wine (an acid-stress environment) and dominate malolactic fermentation. To understand acid tolerance response of O. oeni, a related argG gene was inserted into a plasmid pMG36e and heterologously expressed in Lactobacillus plantarum SL09. The expression levels of the argG gene in L. plantarum were analyzed by RT-qPCR, argininosuccinate synthase activity and cell properties (amino acids, pH, H+-ATPase activity, and ATP levels) were determined at pH 3.7 in comparison with that at pH 6.3. Results showed that the recombinant strain L. plantarum SL09 (pMG36eargG) exhibited stronger growth performance compared with the control strain (without argG gene), and the expression levels of hsp18, cfa, atp, the citrate and malate metabolic genes were apparently increased under acid stress. In addition, the recombinant strain exhibited 11.0-, 2.0-, 1.9-fold higher ASS activity, H+-ATPase activity and intracellular ATP level, compared with the corresponding values for control strain during acid-stresses condition, which may take responsible for the acid tolerance enhancement of the recombinant strain. This is the first work report on heterologous expression of argG gene, and the results presented in this study will be beneficial for the research on acid stress response of O. oeni.